Variations in some trace elements in various degrees of Diabetes mellitus - B.K. Myke-Mbata; S.C. Meludu; G.O. Obochi; J.K. Nnodim (Al Ameen Medical College, 2015)
Background: Diabetes has been shown to be associated with abnormalities in the metabolism of trace elements especially chromium, zinc, copper, magnesium and manganese. Trace element abnormalities has played some role in several complications of diabetes mellitus. Objective: To evaluate serum zinc, copper, chromium and magnesium as indices of chronic complication and compare the parameters among subjects of varying degree of complications. Therefore this work would be evaluating trace element as predictors of chronic complications and establish their relationship with micro albuminuria. Method: It was designed to compare the serum concentration of zinc, copper, chromium and magnesium in the sera of 109 insulin-dependent diabetes mellitus (subjects with no complications, microvascular complications [retinopathy, nephropathy] only and a combination of micro vascular and macro vascular [cardiovascular and neuropathy] complications which were thirty six, thirty seven and thirty six respectively) and 100 non-diabetic healthy control subjects. The mean age of the diabetic patients was similar to that of control. The mean duration of the disease 7.4 +/- 5.8 years (1-15 years) and the mean HbA1c is 9.41± 2.68 in age matched subjects and control. Results: Serum magnesium, and zinc were significantly reduced but copper was significantly increased on comparing with control. Zinc and magnesium has an inverse relationship with copper. Copper and zinc were significantly higher and lower respectively, when subjects with micro and macro vascular complication and micro vascular only are compared with patients without chronic complications. Conclusion: Trace element evaluation, supplementation as well as chelating agent may be helpful in management of Type 2 Diabetes Mellitus patients.